Kontestasi Langgar dan Pesantren (Studi Atas Pranata Keagamaan Lokal di Sumenep Madura) - Ach Khatib ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2016)
This research is a social anthropology study. The theory used is the resistance theory of James C. Scott. The data collection is through interviews, observation, and documentation. This research found: first, the contestation between Langgar Barokah and Pesantren Mathlabul Ulum is not occurred since the beginning of the establishment, but since Mathlabul Ulum established Islamic Elementary School (2003), and then in 2008 founded Langgar Fatimah Binti Ali. Second, contestation occurs in two forms: open and hidden contestation. Contestation appears more hidden, sometimes even symbolic, because they realize that they have role as guide and leader of islamic society, and also they have family relationship. Third, there are five contestants are involved which then narrowed down to two: the contestants of Langgar and pesantren. Fourth, the two contested arena are cultural and economic arenas. Fifth, there are five trigger contestation: negligence of society; differences in patterns of education that should be maintained, Salaf or modern; the legitimacy of the public; and equality preaching territory.